Cervical Cancer Prevention: A Scoping Review of Nursing Implementation Strategies - Agung Subakti Nuzulullail; Magdalena Rindawati; Ika Arif Lidiyana; Avantika Puspa Imelda Wensi; Prisa Tifa Azizah; Anya Bunga Fakhriyah; Wiwin Lismidiati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cervical cancer remains one of the most common cancers among women, with incidence rates continuing to rise. Nurses play an important role in determining strategies to prevent cervical cancer. However, to date, there have been few reviews discussing strategies that nurses can implement to reduce prevalence. This scoping review aims to identify various programs that can be used as nursing interventions in cervical cancer prevention. This scoping review was conducted through PubMed, Science Direct, ProQuest, and EBSCOhost. The selection of studies was based on the PRISMA-ScR 2020 guidelines with the following scheme: (P): Women, Concept (C): Cervical cancer prevention programs, (C): Community and health services. Inclusion criteria included original articles published between 2020 and 2025, Randomized Controlled Trials (RCTs), and quasi-experimental studies. Article quality was assessed using the JBI critical appraisal tool. From 930 records, 13 articles met the criteria. The program was conducted in community and clinical settings such as education, HPV vaccination, screening, information provision, counseling, and training with technology integration strategies such as AI, communication platforms, e-leaflets, social media, and self-sample kits. The program was assessed to be able to increase knowledge, attitudes, participation, and literacy, which can be implemented by nurses.